Molecular networks involved in the immune control of BK polyomavirus - Girmanova, Eva; Brabcova, Irena; Klema, Jiri; Hribova, Petra; Wohlfartova, Mariana; Skibova, Jelena; Viklicky, Ondrej (Clinical & developmental immunology, 2012)
BK polyomavirus infection is the important cause of virus-related nephropathy following kidney transplantation. BK virus reactivates in 30%-80% of kidney transplant recipients resulting in BK virus-related nephropathy in 1%-10% of cases. Currently, the molecular processes associated with asymptomatic infections in transplant patients infected with BK virus remain unclear. In this study we evaluate intrarenal molecular processes during different stages of BKV infection. The gene expression profiles of 90 target genes known to be associated with immune response were evaluated in kidney graft biopsy material using TaqMan low density array. Three patient groups were examined: control patients with no evidence of BK virus reactivation (n = 11), infected asymptomatic patients (n = 9), and patients with BK virus nephropathy (n = 10). Analysis of biopsies from asymptomatic viruria patients resulted in the identification of 5 differentially expressed genes (CD3E, CD68, CCR2, ICAM-1, and SKI) (P < 0.05), and functional analysis showed a significantly heightened presence of costimulatory signals (e.g., CD40/CD40L; P < 0.05). Gene ontology analysis revealed several biological networks associated with BKV immune control in comparison to the control group. This study demonstrated that asymptomatic BK viruria is associated with a different intrarenal regulation of several genes implicating in antiviral immune response.
Keywords: Kidney Diseases; transplantace ledvin; transkriptom; Middle Aged; mužské pohlaví; Biopsy; Adult; Polyomavirus Infections; polyomavirové infekce; Transcriptome; BK Virus; ženské pohlaví; Kidney Transplantation; Humans; virus BK; nemoci ledvin; lidé středního věku; biopsie; dospělí; Female; lidé; Male